Does The Owner Characteristic Affect Sustainability Disclosure And Firm’s Performace? (Empirical Evidence From The Indonesia Stock Exchange) - Ronny Andesto; Zuhal Maftuh Ahnan; Akhmad Saebani (Dinasti Publisher, 2022)
The purpose of this study was to examine the effect of the characteristics of ownership (institutional, foreign, and government) on the sustainability disclosure level and its implications for firm performance. The population of this study is all companies listed on the Indonesia Stock Exchange during 2016-2020. Purposive sampling was used to determine the sample. Data from 35 companies were obtained for hypothesis testing. Path analysis with SPSS v. 25 is used to data processing. The results show that the institutional ownership has a significant and positive effect on the level of sustainability disclosure. Meanwhile, the foreign and government ownership have significant and negative effect on the level of sustainability disclosure. Furthermore, the institutional, foreign, government ownership and sustainability disclosure level have no significant effect on firm performance.